Pelatihan dan Pendampingan Pembuatan Minuman Fermentasi Teh Kombucha sebagai Ide Usaha Di SMKN 1 Wonosari Kabupaten Malang - Kusmiyati, Nur; Kusnadi, Joni; Denta, Anggeria Oktavisa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Based on the results of discussions with vice principal of curriculum section, it shows that there is a need for skills development in field of knowledge and technology. One thing that can be done is training and assistance in making kombucha tea fermented drinks to support agricultural food technology as a business idea at SMKN 1 Wonosari Malang. The purpose of this service activity is to provide knowledge about the theory and method of making kombucha tea fermented drinks. These service activities are carried out using several methods consisting of outreach; demonstrations and practices; guidance followed by mentoring; as well as an analysis of the evaluation of the service program. This training was attended by 30 participants consisting of class XI students at SMKN 1 Wonosari, Malang Regency. The training and mentoring program for making kombucha fermented drinks has been effective. In addition, students of SMKN 1 Wonosari Malang Regency were able to change and improve their knowledge and abilities in making kombucha tea fermented drinks.